2-AZA-[3,3]-Sigmatropic rearrangement and AZA-PRINS cyclization and their applications in total synthesis of (-)-indolizidine-209B and (-)-perhydrohistrionicotoxin - Cheng, Hin Soon (2010)
Two novel C-C bond formation methodologies, i.e. 2-AZA-[3,3]-sigmatropic rerrangement and aza-Prins cyclization, were developed for the synthesis of linear homoallylic hydroxylamines and 2,3,6-trisubstituted piperidines respectively. These two nitrogen-containing compounds are useful building blocks in many natural products. The applications of these methodologies were then demonstrated in the total syntheses of both (-)-indolizidine 209B and (-)-perhydrohistrionicotoxin.